Interactive Domains in the Molecular Chaperone Human αB Crystallin Modulate Microtubule Assembly and Disassembly - Ghosh, Joy G. (Public Library of Science, 2007)
BACKGROUND: Small heat shock proteins regulate microtubule assembly during cell proliferation and in response to stress through interactions that are poorly understood. METHODOLOGY: Novel functions for five interactive sequences in the small heat shock protein and molecular chaperone, human αB crystallin, were investigated in the assembly/disassembly of microtubules and aggregation of tubulin using synthetic peptides and mutants of human αB crystallin. PRINCIPAL FINDINGS: The interactive sequence (113)FISREFHR(120) exposed on the surface of αB crystallin decreased microtubule assembly by ∼45%. In contrast, the interactive sequences, (131)LTITSSLSSDGV(142) and (156)ERTIPITRE(164), corresponding to the β8 strand and the C-terminal extension respectively, which are involved in complex formation, increased microtubule assembly by ∼34–45%. The αB crystallin peptides, (113)FISREFHR(120) and (156)ERTIPITRE(164), inhibited microtubule disassembly by ∼26–36%, and the peptides (113)FISREFHR(120) and (131)LTITSSLSSDGV(142) decreased the thermal aggregation of tubulin by ∼42–44%. The (131)LTITSSLSSDGV(142) and (156)ERTIPITRE(164) peptides were more effective than the widely used anti-cancer drug, Paclitaxel, in modulating tubulin↔microtubule dynamics. Mutagenesis of these interactive sequences in wt human αB crystallin confirmed the effects of the αB crystallin peptides on microtubule assembly/disassembly and tubulin aggregation. The regulation of microtubule assembly by αB crystallin varied over a narrow range of concentrations. The assembly of microtubules was maximal at αB crystallin to tubulin molar ratios between 1∶4 and 2∶1, while molar ratios >2∶1 inhibited microtubule assembly. CONCLUSIONS AND SIGNIFICANCE: Interactive sequences on the surface of human αB crystallin collectively modulate microtubule assembly through a dynamic subunit exchange mechanism that depends on the concentration and ratio of αB crystallin to tubulin. These are the first experimental results in support of the functional importance of the dynamic subunit model of small heat shock proteins.